A note on zeros of orthogonal polynomials generated by canonical transformations (2024)
In this work, the behavior of zeros of orthogonal polynomials associated with canonical spectral transformations of weight functions on $[0,\infty)$ is studied. Namely, by means of standard techniques, we obtain interlacing properties for zeros associated with some particular cases of rational and Christoffel transformations